2007
DOI: 10.1136/jmg.2007.051268
|View full text |Cite
|
Sign up to set email alerts
|

Germline E-cadherin mutations in familial lobular breast cancer

Abstract: Background: The cell surface glycoprotein E-cadherin (CDH1) is a key regulator of adhesive properties in epithelial cells. Germline mutations in CDH1 are well established as the defects underlying hereditary diffuse gastric cancer (HDGC) syndrome, and an increased risk of lobular breast cancer (LBC) has been described in HDGC kindreds. However, germline CDH1 mutations have not been described in patients with LBC in non-HDGC families. This study aimed to investigate the frequency of germline CDH1 mutations in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(92 citation statements)
references
References 27 publications
2
87
0
3
Order By: Relevance
“…However, the CGEMS prostate cancer study showed no evidence of an association with rs9929218 and prostate cancer. Loss of E-cadherin expression is characteristic of invasive lobular breast cancers [34] and germline mutations have been found in some familial lobular carcinomas [35]. There was no evidence of an association between rs9929218 and lobular cancer in the BIGGS cohort, however the study does not have the power to detect such an association if it existed with only 106 invasive lobular cancers in this series.…”
Section: Discussionmentioning
confidence: 54%
“…However, the CGEMS prostate cancer study showed no evidence of an association with rs9929218 and prostate cancer. Loss of E-cadherin expression is characteristic of invasive lobular breast cancers [34] and germline mutations have been found in some familial lobular carcinomas [35]. There was no evidence of an association between rs9929218 and lobular cancer in the BIGGS cohort, however the study does not have the power to detect such an association if it existed with only 106 invasive lobular cancers in this series.…”
Section: Discussionmentioning
confidence: 54%
“…21,22 Disease-causing 16 Even in families without diffuse gastric cancer in their medical history, CDH1 mutations could be found in women with lobular breast cancer. 24 In view of the increased cancer risk, intensified surveillance programmes are indicated. 22,25 For women with neurofibromatosis type I (NF1) (MIM no.…”
Section: Breast Cancer-associated Cancer Predisposition Syndromesmentioning
confidence: 99%
“…Germline CDH1 mutation is the genetic defect underlying some rare cases of hereditary ILBCs [3,8]. Profiling approaches focusing on genomic imbalances established that nearly all ILBCs harbour a loss of 16q22, the locus of CDH1 [9].…”
Section: Introductionmentioning
confidence: 99%